THE POLITICS OF LANGUAGE IN MULTILINGUAL EDUCATION: A Case Study from Timor-Leste - dos Reis, Ana Joana; Feliks, Tans; Tualaka, Dias Pora (Postgraduate School, Universitas Nusa Cendana, 2025)
This study investigates the effectiveness of the Game-Based Learning (GBL) approach inimproving young learners’ vocabulary skills. The research was conducted at Pondok PesantrenDarul Amin Palangka Raya, involving 25 seventh-grade students selected through purposivesampling. A quantitative research method with an experimental group design was employed.The instrument used was a vocabulary test consisting of 15 questions covering five topics:Greetings, Colours, Counting, Telling Time, and Simple Present Tense. Students’ performancewas measured through a pre-test and a post-test. The results showed a significant improvementin students’ vocabulary achievement after the implementation of the Game-Based Learningapproach, with the average score increasing from 66.92 to 87.12. Statistical analysis, includingthe t-test and Kolmogorov-Smirnov normality test, confirmed the effectiveness of thetreatment. These findings suggest that Game-Based Learning is an effective and engagingmethod for enhancing vocabulary acquisition among young learners. The study supports theintegration of game-based strategies as a meaningful and enjoyable alternative to traditionalvocabulary instruction in English language learning.